Do Thai parents discuss sex and AIDS with young adolescents? A qualitative study - Chutima Meechamnan (2018)
This qualitative study explored parents' and young adolescents' perceptions of communication related to sex and HIV/AIDS. Focus group discussions and group discussion were conducted among 67 adolescents and 30 parents. For the adolescents, group discussion using participatory activities was conducted, followed by five focus group discussions. Group discussions using participatory activities were conducted among parents. Thematic analysis indicated that the adolescents received inadequate information about sex and AIDS from their parents, whom they feared as providing negative judgment, and this represented a key barrier to such discussions. Their parents, on the other hand, reported that they believed their children were still too young to learn about and engage in sexual activities. The parents perceived barriers to communication included a lack of confidence and feelings of embarrassment. Nevertheless, they also recognized their important role in their child's sexual education. Collectively, these results draw attention to the need for a culturally appropriate program to strengthen parent-child communication skills for the topics of sex and HIV/AIDS. © 2013 Wiley Publishing Asia Pty Ltd.